CONHECER PARA CONVERTER OU ALGO MAIS?: LEITURA CRÍTICA DAS ETNOGRAFIAS MISSIONÁRIAS DE HENRI-ALEXANDRE JUNOD E CARLOS ESTERMANN - Fiorotti, Silas André (2012)
Colonialism produced several speeches about local cultures, and the discourse of the missionaries is one of its variants and, in turn, are included in this speech the missionary ethnographies. We present a critical reading of two missionary ethnographies produced in Portuguese colonies, the territories of Angola and Mozambique. The first, entitled Usos e costumes dos bantos: a vida duma tribo sul-africana [The Life of South African Tribe], by Henri-Alexandre Junod (1863-1934); the second entitled Etnografia do sudoeste de Angola [The Ethnography of Southwestern Angola], by Carlos Estermann (1896-1976). We problematize the relationship between the missionary action, the Portuguese colonialism and local cultures of these territories of Angola and Mozambique, through the analysis of these missionary ethnographies. These ethnographies, besides presenting the richness of life forms of native societies, signal as they conducted the negotiations between the missionaries in their practices and the natives.